2023
DOI: 10.1177/1759720x231174989
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphy-derived physical activity levels and circadian rhythm parameters in patients with psoriatic arthritis: relationship with disease activity, mood, age and BMI

Abstract: Background: Psoriatic arthritis (PsA) is associated with sleep disturbance, depression and a lifetime risk of obesity and cardiovascular disease. To date, there have been no studies investigating the relationship between objectively-measured physical activity (PA) levels and circadian rhythm disturbance with disease activity, daily symptoms and mood in patients with PsA. Objective: This pilot study aimed to investigate the relationship between disease activity, daily symptoms and mood on PA and circadian rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Similar studies have found similar results to ours: McGagh et al confirmed that patients who did not reach the therapeutic goal of minimal disease activity (MAE) were less physically active. The authors did not show the relationship between the different items that make up MAE ( 13 ). In a recent study by Queiro et al using data from the Spanish registry of new-onset PsA, low physical activity was predictive of moderate or high disease activity at 2 years ( 32 ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar studies have found similar results to ours: McGagh et al confirmed that patients who did not reach the therapeutic goal of minimal disease activity (MAE) were less physically active. The authors did not show the relationship between the different items that make up MAE ( 13 ). In a recent study by Queiro et al using data from the Spanish registry of new-onset PsA, low physical activity was predictive of moderate or high disease activity at 2 years ( 32 ).…”
Section: Discussionmentioning
confidence: 94%
“…Bivariate correlations were calculated between physical activity and DAPSA (and components), HAQ, FACIT-F, PSAID, BMI, HADS-A, HADS-D, and ISI. The linear regression model was performed with exercise as the dependent variable and as independent variables those that had been significant in the univariate analysis and those that, according to the literature, had influenced physical activity (age, sex, BMI, TJC, VAS pain, HADS-A, HADS-D, FACIT-F, and ISI) ( 13 , 14 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through large-scale efforts to measure RARs in hundreds-thousands of community-dwelling subjects (e.g., NHANES [National Health and Nutritional Examination Survey], SOL (Study of Latinos), MESA (Multi-ethnic Study of Atherosclerosis) [13][14][15] ], we know how these parameters vary by sex, age, BMI and active employment 13,14,[16][17][18][19] . Cross-sectional case-control studies have also identified RAR abnormalities in a range of chronic illnesses [20][21][22][23][24][25][26][27][28][29] . Within neuropsychiatry, depression has received the greatest emphasis, with multiple studies linking the severity of prevalent depression symptoms to reductions in robustness/routines (low F and IS, high IV), amplitude and a delayed acrophase 12,16,[30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%